Analysis and forecasting of seasonal fluctuations in budget revenues of different levels under martial law as a component of effective public finance management in Ukraine (Economics and region, 2024)
The purpose of the article is to analyse and forecast seasonal fluctuations in tax revenues to the State Budget of Ukraine from Volyn region, as well as to local budgets of Volyn region. In 2022–2023, the State Budget of Ukraine received the largest amount of funds from VAT on goods imported into the customs territory of Ukraine; customs duties on goods imported by business entities; excise tax on vehicles imported into the customs territory, as well as PIT paid by tax agents on taxpayer's income in the form of wages; and military PIT. The local budgets of Volyn region received the largest share of these payments: PIT; military PIT; single tax on individuals; land tax on legal entities; rent on legal entities. For eight tax revenue indicators (except for military PIT), linear trend models were built, forecast annual data for 2024 were obtained, which, in turn, served as the basis for calculating the corresponding seasonal indicators.
Keywords: State Budget of Ukraine; local budgets; Volyn region; tax payments; analysis; seasonality indices; trend models; forecasting